2009
DOI: 10.1021/cm9001465
|View full text |Cite
|
Sign up to set email alerts
|

Composition−Structure−Property Relationships of 6H- and 12R-Type Hexagonal Ba(Mn,Ti)O3−δPerovskites

Abstract: The crystal structures of 6H-type BaMn 0.15 Ti 0.85 O 3 , BaMn 1/4 Ti 3/4 O 2.95 , and BaMn 1/2 Ti 1/2 O 2.84 and 12Rtype BaMn 2/3 Ti 1/3 O 3 have been established by a combination of X-ray, neutron, and electron diffraction, and high-resolution electron microscopy. The 6H-type structure (space group P6 3 /mmc) can be described by a stacking sequence (hcc) 2 along the c-axis with any anion deficiency located exclusively in the h-BaO 3 layers. Ti atoms display a strong preference for the corner-shared octahedra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 33 publications
10
26
0
Order By: Relevance
“…A good agreement of the atomic positions and bond distances is found with respect to previously published data [8,21]. Table I: Refined structural parameters and relevant bond lengths for BaTi 1/2 Mn 1/2 O3 at room temperature.…”
Section: A Xas and Neutron Diffractionsupporting
confidence: 83%
See 1 more Smart Citation
“…A good agreement of the atomic positions and bond distances is found with respect to previously published data [8,21]. Table I: Refined structural parameters and relevant bond lengths for BaTi 1/2 Mn 1/2 O3 at room temperature.…”
Section: A Xas and Neutron Diffractionsupporting
confidence: 83%
“…A 12R-type perovskite structure was employed in the refinement, see Fig 3(a). It consists of face-sharing trimers of octahedra connected by corner-sharing octahedra along the c axis, under the space group R3m [8,21]. All atomic occupancy factors were fixed at the stoichiometric values in our Rietveld refinement of the Neutron diffraction data.…”
Section: A Xas and Neutron Diffractionmentioning
confidence: 99%
“…From dw/dT as a function of temperature, the paramagnetic-antiferromagnetic transition temperature T c was determined to be 11.7 K. ZFC and FC curves diverge at about 50 K, indicating history dependence of magnetization.Similar divergence was also found in Sr(Ti 1/2 Mn 1/2 )O 3 [18] and Ba(Ti 1/2 Mn 1/2 )O 3 . Miranda et al [19] suggested that the magnetic transition of undetectable impurity Mn 3 O 4 should be responsible for this feature. In Fig.…”
Section: Magnetic Properties Of Ctmmentioning
confidence: 99%
“…ABO 3 perovskites have attracted considerable attentions for their superior electrical properties [1,2], such as ferroelectric, piezoelectric, and microwave dielectric properties. In the latter case, many cubic perovskites have been extensively studied [3][4][5] for their applications at microwave frequency.…”
Section: Introductionmentioning
confidence: 99%
“…And the structurecomposition-property relationships among them have been established. In recent years, some researches have been focused on the hexagonal perovskites for their interesting crystal structures and special physical properties [2,6]. But the formation mechanism of the hexagonal perovskites and the relationships between structures and properties are still not well clear.…”
Section: Introductionmentioning
confidence: 99%